2015
DOI: 10.3850/s2382581215000149
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic studies on Zingiber (Zingiberaceae) in China I: Zingiber kerrii and the synonymy of Z. menghaiense and Z. stipitatum

Abstract: A general introduction to Zingiber is provided, along with an outline of the materials and methods used in this paper and which are to be used in our subsequent taxonomic studies on Zingiber in China. Based on an investigation of the protologues, and on comparisons of both the type specimens and living materials collected from the type localities and their immediate vicinities. Zingiber stipitatum S.Q.Tong and Z. menghaiense S.Q.Tong are here reduced to synonymy under Z. kerrii Craib. A previous lectotypificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…The materials and methods for this study follow those of our work on Zingiber in China (Bai & al., 2015a). Names particularly relevant to the current study were identified based on the protologues, all previously published taxonomic works dealing with the genus Zingiber, regional flora treatments and various databases, e.g., Zingiberaceae Resource Centre , World Checklist of Selected Plant Families (Govaerts & al., 2018) and Tropicos (2019).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The materials and methods for this study follow those of our work on Zingiber in China (Bai & al., 2015a). Names particularly relevant to the current study were identified based on the protologues, all previously published taxonomic works dealing with the genus Zingiber, regional flora treatments and various databases, e.g., Zingiberaceae Resource Centre , World Checklist of Selected Plant Families (Govaerts & al., 2018) and Tropicos (2019).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A more detailed introduction to Zingiber and its currently accepted sectional classification, with a focus on the species in China, is given in Bai & al. ().…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The terminology follows Beentje (2012) and our recent works cited above. The recognition of labellum and lateral staminodes as separate structures and the methodology of their measurements follow the recent work of Bai et al (2015). Similar to Zingiber emeiense Z.Y.Zhu in having purple-white flowers, but differs in the narrowly ovate to narrowly elliptic leaves (15-20 × 3.5-4 cm), short ligules (c. 1-2 mm, shallowly bilobed), pure white corolla lobes, purple to dark violet labellum with white blotches and pure white lateral staminodes (vs. laminae 25-35 × 6-9 cm; ligules papery, bifid, c. 7 mm long; red corolla lobes, and both labellum and lateral staminodes purple).…”
Section: Introductionmentioning
confidence: 99%